Truth and Eros : Foucault, Lacan and the question of ethics. - Rajchman, John (Rouledge Library Editions: Michel Foucault., 2013)
In this reissused work, first published in 1991, John Rajchman isolates the question of ethics in the work of Foucault and Lacan and explores its ramifications and implications for the present day. He demonstrates that the question of ethics was at once the most difficult and the most intimate question for these two authors, offering a complex point of intersection between them. As such, he argues that it belongs to the great tradition that is concerned with the passion or eros of philosophy and of its ""will to truth"". Truth and Eros suggests a way of reading Foucault and L.